Analisis Kebijakan Pengadaan Ruang Terbuka Hijau melalui Perda Nomor 10 Tahun 2012 tentang Rencana Tata Ruang Wilayah Kabupaten Tegal Tahun 2012-2032 - Muhammad Salim .; Puji Astuti . (Journal of Politic and Government Studies, 2017)
Green Open Space is a need for each region of the area, where the provisions stipulated in the Act No. 26 of 2007 on Spatial Planning. Each district / city is expected to meet the percentage of green space area that is 30% which is divided into 20% public and 10% private. Tegal regency, according to existing data, which is owned green space area have not reached 30%. So this study is intended to examine more deeply linked Tegal regency government regulations relating to the procurement of green open space, through Regulation No. 10 Year 2012 on Spatial Planning Tegal Year 2012-2032.This research was conducted using qualitative methods descriptive type, using existing data and documents, as well as extracting information from the government sector and civil society, who will explain the detail of the real state. As well as using triangulation types Triangulasai Source Data to compare the data document with the results of indepth interviews.Of all the research that has been done, it can be seen that the lack of policy consistency and a lack of compliance with the zoning of green open space scattered throughout the district, as well as the implementation of which is considered less than optimal (the role of actor and policy targets), and an indicator that determines success have not been fully considered. Keywords: Green Open Space, Policy, Implementation.